Exploring the Clinical Applications of Lemongrass Essential Oil: A Scoping Review - Ikhwan Yuda Kusuma; Muhammad Iqbal Perdana; Csaba Vágvölgyi; Dezső Csupor; Miklós Takó (MDPI AG, 2024)
Lemongrass is a medicinal plant that produces essential oil with a variety of therapeutic properties. Although lemongrass essential oil (LGEO) is promising in clinical applications, the existing knowledge on the efficacy and safety of LGEO remains limited. This scoping review aimed to identify, summarize, and synthesize existing literature related to the clinical applications of LGEO to provide an overview of its potential therapeutic benefits for patients. Three databases (PubMed, Web of Science, Scopus) were used following the PRISMA-ScR guidelines to find articles published between 1 January 2013, and 1 November 2022. A total of 671 records were identified and 8 articles were included in this scoping review. The majority of patients received oromucosal and topical treatment. The results of the studies suggest that LGEO might be a useful tool in the treatment of periodontitis, gingivitis and oral malodour, with similar efficacy to chlorhexidine (anti-gingivitis effect) and doxycycline (periodontitis). Additionally, LGEO has the potential for treating pityriasis versicolor and preventing skin aging and may have anti-dandruff effects. These findings not only underscore the diverse clinical potential of LGEO but also emphasize its comparable efficacy to established treatments. Further research is imperative to comprehensively evaluate LGEO's effectiveness, safety, mechanisms of action, potential interactions with other medications, and its long-term tolerability across diverse populations.